Lead-oriented synthesis: Investigation of organolithium-mediated routes to 3-D scaffolds and 3-D shape analysis of a virtual lead-like library. Issue 11 (1st June 2015) - Lüthy, Monique; Wheldon, Mary C.; Haji-Cheteh, Chehasnah; Atobe, Masakazu; Bond, Paul S.; O'Brien, Peter; Hubbard, Roderick E.; Fairlamb, Ian J.S.
Graphical abstract: Abstract: Synthetic routes to six 3-D scaffolds containing piperazine, pyrrolidine and piperidine cores have been developed. The synthetic methodology focused on the use of N -Boc α-lithiation-trapping chemistry. Notably, suitably protected and/or functionalised medicinal chemistry building blocks were synthesised via concise, connective methodology. This represents a rare example of lead-oriented synthesis. A virtual library of 190 compounds was then enumerated from the six scaffolds. Of these, 92 compounds (48%) fit the lead-like criteria of: (i) −1 ⩽  A  log  P  ⩽ 3; (ii) 14 ⩽ number of heavy atoms ⩽ 26; (iii) total polar surface area ⩾ 50 Å 2 . The 3-D shapes of the 190 compounds were analysed using a triangular plot of normalised principal moments of inertia (PMI). From this, 46 compounds were identified which had lead-like properties and possessed 3-D shapes in under-represented areas of pharmaceutical space. Thus, the PMI analysis of the 190 member virtual library showed that whilst scaffolds which may appear on paper to be 3-D in shape, only 24% of the compounds actually had 3-D structures in the more interesting areas of 3-D drug space.